ANALISIS PENGARUH VALUE FOR MONEY AUDIT TERHADAP AKUNTABILITAS PADA INSPEKTORAT BENGKULU TENGAH - Karnadi karnadi (Creative Research Management Journal, 2018)
Value for money audit is performance measurement that is in the local government.value for money audit consists of the audit economic efficiency and effectiveness of which is basically the expansion of the financial statements in terms of goals and procedures. While accountability is an obligation the holder of trust (agent) to provide the responsibility, presentation,reported dang expressed all activities and activities be responsible for the giver mandate (principal) that has and authority to ask for accountability it. The purpose of this study is to test and analyze the influence of value for money audit inspectorate Bengkulu Tengah. This study using a sample of 30 audit team on inspectorate Bengkulu Tengah. Data collection done for one week at the 11th until april 18 2018 by providing koesioner. The result of data processing obtained coefficient of determination of 0,189 or 18,9% correlation or relationship of 0,435. And significant value for money for 0,016. So of these results indicate that there is a relationship and significant effect between the value for money audit of accountability in inspectorate Bengkulu Tengah to the value of the influence of 18,9%.